Model Experimental Study on Stress Transfer and Redistribution in a Clay Landslide under Surcharge Load - Heng-Jun Hou; Bo Wang; Quan-Xiang Deng; Zheng-Wei Zhu; Feng Xiao (Advances in Materials Science and Engineering)
Stress transfer and redistribution always accompany with the evolution of landslides. However, previous literature studies have mainly focused on stages of stress variation, and far too little attention has been paid to detailed transfer and redistribution process analysis on stress variation. In this paper, a large-scale clay model slope with masonry slide bed and prefabricated cambered slip surface was constructed. Earth pressure cells were embedded into slip mass to monitor vertical and horizontal stresses in different parts of the test soils under the set load sequence. Stress transfer efficiency (STE) indicators based on qualified stress monitoring datasets (tested by Shapiro-Wilk method) were established to quantify the stress transfer process. Staged development of stress inside the clay slope was analyzed through extracting slopes of stress curves and limit loads. The stress redistribution process was analyzed using STE and deflection of stress isolines derived from numerical simulation. Moreover, to study the influence of loading position on stress variation, geometry partitioning has also been discussed. Results showed that vertical and horizontal stresses had different growth trends on both sides of 80 kN and 60 kN, respectively. Horizontal stress growth has two stages; vertical stress growth has two stages in soils close to slope surface and shear outlet, while there are three stages in other soils. Vertical stress transfer efficiency (VSTE) and horizontal stress transfer efficiency (HSTE) are recommended to quantify stress transfer and redistribution process. Based on VSTEs and HSTEs, the slip mass could be partitioned into three parts: loading zone, transfer zone, and free zone. Deflecting amplitudes of stress isolines were in consistency with the results revealed by STEs.